2021
DOI: 10.1128/aac.02461-20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Baseline Enterobacterales and Pseudomonas aeruginosa Isolates from a Phase 3 Nosocomial Pneumonia (ASPECT-NP) Clinical Trial

Abstract: We evaluated β-lactam-resistant Enterobacterales species and Pseudomonas aeruginosa baseline lower respiratory tract isolates collected during the ASPECT-NP phase 3 clinical trial evaluating the safety and efficacy of ceftolozane-tazobactam compared with meropenem for treatment of ventilated nosocomial pneumonia in adults. Isolates were subjected to whole genome sequencing, quantitative real-time PCR for quantification of the expression levels of β-lactamase and efflux genes, and Western blot analysis for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The results showed that a large percentage of strains decreased their MIC to CZA and C/T in the presence of the efflux pump inhibitor, PAβN, but most of them were minor changes (RND 2x) and insufficient to increase the proportion of susceptible strains in this population. This may indicate that the effectiveness of the RND-mediated efflux of CZA and C/T is generally low compared with other antibiotics, consistent with previous reports ( Cabot et al, 2014 ; Castanheira et al, 2014 ; Castanheira et al, 2021 ). In fact, the changes observed at the population scale in susceptibility to CZA due to the presence of PAβN were not significant, opposite to C/T, for which these changes were significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results showed that a large percentage of strains decreased their MIC to CZA and C/T in the presence of the efflux pump inhibitor, PAβN, but most of them were minor changes (RND 2x) and insufficient to increase the proportion of susceptible strains in this population. This may indicate that the effectiveness of the RND-mediated efflux of CZA and C/T is generally low compared with other antibiotics, consistent with previous reports ( Cabot et al, 2014 ; Castanheira et al, 2014 ; Castanheira et al, 2021 ). In fact, the changes observed at the population scale in susceptibility to CZA due to the presence of PAβN were not significant, opposite to C/T, for which these changes were significant.…”
Section: Discussionsupporting
confidence: 91%
“…These highlights the need to apply a modified intrinsic resistance concept that can be advantageous when clinical isolates are studied, named here as “baseline susceptibility”. It has been reported that modification and/or overexpression of the RND efflux pumps are implicated in acquired resistance to CZA and C/T in Non-CP-CRPA, usually in combination with other mechanisms of beta-lactam resistance such as the oprD decrease expression, PBPs modification or ampC overexpression ( Castanheira et al, 2014 ; Wi et al, 2018 ; Castanheira et al, 2021 ; Gomis-Font et al, 2021 ). In particular, the overexpression and/or structural modification of MexAB-OprM is the most common RND-mediated mechanism observed in acquired resistance to CZA and C/T ( Castanheira et al, 2014 ; Wi et al, 2018 ; Gomis-Font et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this study is that molecular characterization of the resistant isolates was not performed. There have been recent publications describing the mechanisms of ceftolozanetazobactam resistance in P. aeruginosa , which include the acquisition of extended-spectrum or metallo-β-lactamases, mutations in chromosomal AmpC ( Pseudomonas -derived cephalosporinase), and/or mutations in the outer membrane porin, OprD ( Fraile-Ribot et al, 2018 ;Castanheira et al, 2021 ;Simner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The golden standard of nucleic acid detection is qPCR. qPCR specifically and accurately identifies K. pneumoniae from bacteria like E. coli and S. aureus [19] and its antibiotic-resistant genes, such as ESBL-encoding and Fosfomycin-encoding genes [20]. However, qPCR needs expensive equipment and skilled workers [21].…”
Section: Discussionmentioning
confidence: 99%